PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PENEMUAN TERBIMBING (GUIDED DISCOVERY) DENGAN PENDEKATAN SOMATIC, AUDITORY, VISUAL, INTELLECTUAL (SAVI) PADA MATERI POKOK PELUANG KELAS IX SMP TAHUN PELAJARAN 2013/2014 - Yusnita Rahmawati; Mardiyana Mardiyana; Sri Subanti (Jurnal Pembelajaran Matematika, 2014)
Abstract : The purposes of this study were to: (1) develop a valid learning device based on guided discovery with Somatic, Auditory, Visual, Intellectual (SAVI) especially on Probability, and (2) know the effectiveness of learning device which was developed based on guided discovery with Somatic, Auditory, Visual, Intellectual (SAVI). The study was an educational research and development used 4D model with the steps of model: (1) defining, that consists of: starting and ending analysis, student analysis, learning analysis, task analysis, and learning objectives specification; (2) designing; (3) developing; and (4) disseminating. Test for knowing the effectiveness of the learning device was conducted with the population of this study was all students in grade IX of SMP Negeri 6 Surakarta. Before carrying out the study, balanced test was performed using t – test on two groups of populations. The data analysis technique which was used to test the hypothesis was t – test. Pre-requisite test was performed with Lilliefors method to test the normality and Bartlett methods to test the homogeneity. The results of this study were as follows. (1) A valid learning device based on guided discovery with Somatic, Auditory, Visual, Intellectual (SAVI) have been developed that consists of (a) Lesson Plan, (b) Student’s Worksheet, (c) Student’s Book, (d) Teacher’s Handbook, and (e) Test of Learning Result; (2) The result of the effectiveness test showed that the mathematics learning result of the students who attended on guided discovery learning with Somatic, Auditory, Visual, Intellectual (SAVI) by using the learning device was better than that of students who attended on learning by method which was usually used by the teacher.Keywords : Development, Learning Device, Guided Discovery, Somatic, Auditory, Visual, Intellectual (SAVI).